Climate bottlenecks off Newfoundland and Labrador for Atlantic cod in relation to eastern Canadian marine protected areas - Julie A. Thayer; Trond Kristiansen; Cassandra A. Konecny; Gammon Koval; Rodd Laing; David Côté (Canadian Science Publishing, 2024)
Climate change presents challenges for marine area-based conservation measures through altered habitat and associated species range shifts. We conducted statistical downscaling for the eastern Canadian coastal domain over a range of global climate models, focusing on habitat suitability for Atlantic cod (Gadus morhua), a numerically depressed, but ecologically, economically, and culturally important species in this region. We examined cod egg survival, juvenile growth, and spawning habitat suitability, combining these into one habitat index to compare within-closure habitat suitability for multiple life stages through time. Areas of high cod egg habitat suitability are projected to shift northward and increase across all area closures studied, while optimum juvenile habitat shifts north and eastward, increasing in almost all closures except the south. Spawning habitat as a function of temperature and oxygen will likely decrease through time across the entire region, but less in northern locations. Overall cod habitat is forecasted to decline in the south of the region while increasing at central and northern latitudes, highlighting the importance of existing and developing northern shelf area closures. While warming will bring temperatures closer to optimum levels for cod in this cold-water system, oxygen limitation will become more prevalent in the south of the region and should be monitored as an important ocean health indicator.